The role and place of energy in ecological legal regulation (International relations and international law Journal, 2016)
In this article the author examines the energy in the context of ecological – legal regulation object. Stressing the need for strategic energy to humanity author also raises the question of energy legal explore. In accordance with a modern understanding energy doesn`t introduce material thing, but is a boon which has the capacity to meet human needs. Author sets specific objectives to achieve the objectives of the study, which are made as a result of the conceptual conclusions. In conclusion the author marks the need of ecology energetic resource concept interpretation for integration of ecology and energetic legislation. As the main result we can note that the energy directly acts as the object of environmental relationship.
Keywords: energy; energetism; natural resources; energy resources; energy legislation